DIFERENÇAS NO CONSUMO ALIMENTAR DE ADOLESCENTES NA REGIÃO CENTRO-OESTE E OUTRAS REGIÕES BRASILEIRAS - Ruanda Pereira Maia; Muriel Bauermann Gubert; Stefanie Eugênia dos Anjos Coelho Kubo (Universidade do Estado do Rio de Janeiro, 2014)
The study aimed to analyze the frequency of consumption ofhealthy and unhealthy foods and differences in knowledge andconsumption of typical Brazilian food among adolescents inthe Midwestern region, as compared to other regions. This is across-sectional study conducted with 10,514 adolescents, aged13 and 14, who responded to an online questionnaire. Datawere analyzed with the software package SPSS statistical, usingunivariate analysis to estimate the frequency of dietary intakeand the chi-square test for the categorical variables knowledgeand consumption of Brazilian food. The level of significance was5%. High frequency consumption of unhealthy foods and lowfrequency consumption of unhealthy foods were both observed.Adolescents from the Midwestern Region had higher frequencyof consumption of beans and vegetables and lower frequencyof consumption of fried snacks and cookies, with significantdifference (p < 0.001) for the other regions. National foodswere widely known, except for sweet yam, which only 32.1%of adolescents in the Midwest Region reported being familiarwith. Consumption of these typical foods was really varied anddiffered significantly from other regions for sweet yam, tripestew, cassava, dried beef rice, canjica and grape. Further detailedresearch is needed on food consumption in households and aswell as studies on consumption that include the achievement ofFood and Nutritional Safety standards. DOI 10.12957/demetra.2014.7286